2014
DOI: 10.1016/j.jpeds.2014.01.060
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin Uridine Diphosphate-Glucuronosyltransferase Variation Is a Genetic Basis of Breast Milk Jaundice

Abstract: Objective To evaluate the role of bilirubin UDP-glucuronosyltransferase family 1, polypeptide A1 (UGT1A1) gene variations on prolonged unconjugated hyperbilirubinemia associated with breast milk feeding (breast milk jaundice [BMJ]). Study design UGT1A1 gene allelic variation was analyzed in 170 Japanese infants with BMJ with polymerase chain reaction-direct sequencing, and their genotypes compared with serum bilirubin concentrations. In 62 of 170 infants, serum bilirubin concentration was followed after 4 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 35 publications
2
43
0
2
Order By: Relevance
“…UGT1A1*28 enhancer-promoter reduces the expression of hepatic UGT1A1 but not intestinal UGT1A1 at neonatal period. 33 However, UGT1A1*28 does not only affect hyperbilirubinemia in the neonatal period; 5,21 in this study, it was clinically revealed that UGT1A1*28 plays a role in GS after puberty, similar to UGT1A1*6, in the Japanese population.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…UGT1A1*28 enhancer-promoter reduces the expression of hepatic UGT1A1 but not intestinal UGT1A1 at neonatal period. 33 However, UGT1A1*28 does not only affect hyperbilirubinemia in the neonatal period; 5,21 in this study, it was clinically revealed that UGT1A1*28 plays a role in GS after puberty, similar to UGT1A1*6, in the Japanese population.…”
Section: Discussionmentioning
confidence: 52%
“…Our recent and previous studies on the association between neonatal jaundice revealed that UGT1A1*6 is also a risk factor for neonatal hyperbilirubinemia in early neonatal period and a genetic cause for BMJ. 4,5,21 However, UGT1A1*28 does not contribute to neonatal hyperbilirubinemia and BMJ. The reason why the contribution of UGT1A1*28 to generate hyperbilirubinemia is different in neonatal period and thereafter was estimated as follows.…”
Section: Discussionmentioning
confidence: 97%
“…В течение последних 5 лет представлены доказа-тельства того, что имеется связь между желтухой есте-ственного вскармливании и вариантами гена, кодирую-щего синтез фермента уридин-дифосфат-глюкуронил-трансферазы (UDP-glucuronosyl-transferase family 1, polypeptide A1 [UGT1A1]), участвующего в конъюгации непрямого билирубина [11]. При желтухе от материнского молока в неонатальном периоде наиболее часто встреча-ется аллель UGT1A1*6.…”
Section: рисунок 3 фридрих теодор фрерихс (Friedrich Theodor Von Frunclassified
“…Один или несколько компонен-тов в молоке могут вызвать желтуху именно у младенцев, у которых имеются такие мутации. Таким образом, дли-тельная неконъюгированная гипербилирубинемия может развиваться у младенцев с UGT1A1 * 6, которые получа-ют грудное молоко [22,23]. При желтухе, связанной с составом грудного молока, наблюдается более высокая концентрация НБ в крови к 4-6-му дню жизни, которая продолжает нарастать, достигая пика к 10-15-му дню жизни.…”
unclassified